Globalization: Can Africa Benefit From Its Promises? - Unya , Ikenna Ukpabi; Okorie, Martha (Kashere Journal of Politics and International Relations, 2024)
The phenomenon of globalization is having a major impact on systems around the world. The promoters argue persuasively that globalization will lead to global stability, reduction of poverty and inequalities within and among nations and a higher standard of living for all. However, experience on ground has shown otherwise. The third world countries especially those in African region have been made vulnerable. Instead of becoming more integrated into the world economy, Africa has been largely marginalized and excluded from the real benefits of globalization. Thus, this study aims at comprehensively investigating the implications of globalization in the economic development of Africa. Basically, the study is qualitative, utilizing mostly secondary source of data such as books, journals, newspaper articles, conference papers, internet publications, among others; all considered relevant in understanding the issue of globalization and its implications in Africa. The findings of the study reveal that globalization has raised some troubling concerns for a developing continent like Africa. And that since Africa’s economies are not competitive and lacking in technological innovations, it may be difficult for the region to maximize or access the full benefits of globalization. The study, thus, concludes by recommending among other things that Africa must position itself appropriately by making serious internal political and economic restructuring; deepening regional integration by creating a single market and investing on digital infrastructure which will make Africa visible in global trade regime as a respected participant.